Do People Perceive Products Differently When Buying for Self-versus for Others? Malleable Brand Personality in Gifting - Sussan, Fiona; Nakagawa, Hideyuki (European Scientific Journal, ESJ, 2023)
Depending on situation, a person’s role identity can be activated and impacts their behavior accordingly. There is a lack of research investigating identity salience within the context of gifting and its subsequent impact on the perceived brand personality of a gift in different gifting situations. This paper proposes that in others-gifting situation, a social identity is activated leading to a change in perceived brand personality of the same product that is purchased for self-gifting. Within the Japan context, we hypothesize that excitement brand personality dimension is more prominent in self-gifting than in others-gifting, while competence and sincerity brand personalities are more prominent in others-gifting than in self-gifting scenario. To test these hypotheses, thirty-six brand personality traits (Aaker et al., 2001) of eight brands were evaluated by 251 respondents in Japan. Factor analysis and multiple regression results support the main hypotheses. These nuanced findings have meanings for brand managers.